Judicial Review Mahkamah Konstitusi Terhadap Pasal Pencemaran Nama Baik dalam UU ITE: Antara Perlindungan Reputasi dan Kebebasan Berekspresi di Era Digital - Wilma Silalahi; Adelia Nelma Mutiara (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
The rapid growth of information and communication technology has shifted the public sphere into a digital domain, thereby broadening opportunities for people to express their views. In Indonesia, however, this expansion of expressive space has been accompanied by the increasing use of the Electronic Information and Transactions Law (UU ITE), particularly its defamation provisions, which has sparked intense debate regarding the boundary between reputation protection and freedom of expression. The issue has become more pressing because the norm is often perceived as ambiguous, susceptible to overcriminalization, and capable of producing a chilling effect within digital democracy. This study is intended to critically examine the Constitutional Court’s judicial review of the defamation provisions under the UU ITE and to explore how the relationship between reputation protection and freedom of expression is constructed in the Court’s reasoning. The research adopts a normative juridical method through statutory, case, and conceptual approaches. Data were gathered through library research and documentation of legislation, Constitutional Court decisions, and relevant scholarly works, and subsequently analyzed using a qualitative descriptive-analytical method. The findings indicate that the normative construction of defamation under the UU ITE still raises problems of legal certainty and proportionality in restricting rights, even though Constitutional Court Decision Number 105/PUU-XXII/2024 has narrowed the scope of protected subjects. This study concludes that reformulating the UU ITE provisions, strengthening non-penal approaches such as restorative justice, and fostering a more progressive role of the Constitutional Court are essential steps toward building a fair, proportionate, and democracy-compatible legal system in Indonesia’s digital era.